Halide solid electrolyte and preparation method and application thereof

By introducing high -priced transition metal elements B and A in the introduction of halide solid -state electrolytes, the concentration of lithium ions and vacancy is regulated to solve the problems of low and low processing of the existing halide solid electrolyte. The new type of halide is solid -state electrolyte, which improves battery performance and application value.

CN119381528APending Publication Date: 2025-01-28SUN YAT SEN UNIVERSITY SHENZHEN +1

Patent Information

Application Number
CN202411490878.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing halide solid electrolytes have low ionic conductivity, complex preparation process and high cost, making it difficult to achieve large-scale commercial application.

Method used

By introducing high -priced transition metal element B (TA, NB) with high -priced cation A (YB, Y, HF), the concentration of lithium ions and vacant levels is regulated, lithium space, reduces crystallization, and improves the conductivity.

Benefits of technology

It significantly improves the ion conductivity of the halide solid electrolyte, up to 4ms/cm above 4ms/cm, reducing the preparation cost, and increasing the cycle life and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381528A_ABST
    Figure CN119381528A_ABST
Patent Text Reader

Abstract

The invention relates to a halide solid electrolyte and a preparation method and application thereof, and belongs to the technical field of solid electrolytes. The halide solid electrolyte provided by the invention is Li < 1 + (5-n) < x > A < x > B < 1-x > Cl < 6 >, A is at least one of Yb, Y and Hf, and B is at least one of Ta and Nb; wherein n is the valence of the doping element, and n is equal to 3 or 4; according to the halide solid-state electrolyte, the proportion of doped elements is regulated and controlled, the ionic conductivity is improved, the highest ionic conductivity can reach 4 mS / cm or above, the cycle performance is improved, the preparation process is simple, the cost needed by commercial production is reduced, and the halide solid-state electrolyte has high application value in large-scale production of solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid electrolytes, and in particular to a halide solid electrolyte and a preparation method and application thereof. Background Art

[0002] As global concern about climate change deepens, there is an urgent need to find ways to reduce greenhouse gas emissions. New energy technologies such as wind power and solar energy are clean and environmentally friendly and have become an important part of this transformation. The development of energy storage technology has spawned the development of high-performance batteries. Safer and high-performance commercial batteries are the goals that the industry and scientific research community are eager to pursue. High-performance solid electrolytes and safe, high-energy-density metal lithium batteries have become research hotspots. Oxide solid electrolytes have a very wide electrochemical window (0-5V vs. Li / Li + ), but its ionic conductivity rarely exceeds 1mS / cm. At the same time, due to the hardness of the oxide, the contact with the positive and negative electrodes is poor; sulfide solid electrolytes have the highest ionic conductivity (22mS / cm) and excellent deformability, but their electrochemical window is narrow (1.7V-2.8V) and their wet air stability is poor (easy to react with water in the air to generate toxic hydrogen sulfide gas).

[0003] Halide solid electrolytes have attracted extensive attention due to their good deformability, good compatibility with high-voltage positive electrodes, and good lithium ion conductivity. However, only a few halide solid electrolytes have room temperature ion conductivity exceeding 1mS / cm, and the raw materials used to prepare them contain relatively expensive rare earth elements and the preparation conditions are relatively harsh, making them unable to be commercially applied on a large scale (Li3InCl6, Li3ScCl6, Li3ErCl6).

[0004] CN116344924A discloses a halide solid electrolyte [Li 3-(z-3)x M 1-x N x ] 6+ [A a B b ] 6- ,M is selected from Y 3+ 、V 3+ Cr 3+ , N is selected from Hf 4+ , 5+ , A and B are selected from halogens. Although its ionic conductivity is greater than 1 mS / cm, the time required for its preparation is 30h-50h, and the time cost of large-scale production is relatively high. CN110970667A discloses a halide solid electrolyte Li3YCl containing Y x Br 6-x, the conductivity can be as high as 1 mS / cm, but due to the presence of Br ions, the stability under high voltage is poor.

[0005] Therefore, there is an urgent need to develop a new type of halide solid electrolyte with simple preparation process, low cost, high ionic conductivity and improved battery performance, which is of great significance to the high-performance battery industry and research and development. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a halide solid electrolyte and its preparation method and application. To achieve the above purpose, the technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a halide solid electrolyte, wherein the halide solid electrolyte is Li 1+(5-n)x A x B 1-x Cl6, A is at least one of Yb, Y, and Hf, B is at least one of Ta and Nb; n=3 or n=4; 0.1≤x≤0.9.

[0008] The present invention is based on the substitution of the metal sites of the transition metal layer in the halide electrolyte by using a high-valent transition metal element B (Ta, Nb): a transition metal element A (at least one of Yb, Y, Hf, with a valence of n=3 or n=4) in a specific ratio and a high-valent cation Ta 5+ , Nb 5+ By combining the two, by regulating the lithium ion concentration and vacancy concentration in the halide solid electrolyte, more lithium vacancies are added and the crystallinity of the halide solid electrolyte is reduced, so that lithium ions are transported in the entire three-dimensional ion transport lattice network, and the transmission distance between layers and between lithium ions in the same layer is shortened; at the same time, the increased amorphous degree of the halide solid electrolyte, the disorder of the transition metal cations and the distortion of the lattice reduce the potential barrier required for the overall lithium ion transmission, which is beneficial to significantly improve the ionic conductivity of the halide solid electrolyte.

[0009] When only a single transition metal cation A is introduced without introducing a high-valent transition metal element B, the ionic conductivity of the solid electrolyte is low, with a maximum of only 0.22 mS / cm.

[0010] Compared with the reported halide solid electrolytes containing rare earth metal elements, the new halide solid electrolyte provided by the present invention has a higher ionic conductivity (maximum ≥ 4mS / cm). In addition, the electronic conductivity of the halide solid electrolyte in the present invention has also decreased by an order of magnitude, which can achieve a longer cycle life during the use of the battery. At the same time, the present invention uses relatively cheap transition metal ions, which can also reduce the cost required for commercial production; the halide solid electrolyte of the present invention is applied to the preparation of solid-state battery positive electrode materials and electrolytes, which can effectively improve the energy density of all-solid-state batteries, and has excellent battery performance at a high rate of 2C, which helps to increase the total energy of new energy vehicle battery packs and improve the pure electric cruising range, and has extremely high application value.

[0011] Preferably, the room temperature ionic conductivity of the lithium ion halide solid electrolyte material is 0.80 mS·cm -1 、0.85mS·cm -1 、0.87mS·cm -1 、0.93mS·cm -1 、0.96mS·cm -1 、1.02mS·cm -1 、1.52mS·cm -1 、1.75mS·cm -1 、1.98mS·cm -1 、3.74mS·cm -1 、4.50mS·cm -1 The range value of one or both of them.

[0012] Preferably, A is at least one of Yb and Hf, and B is at least one of Ta and Nb.

[0013] More preferably, the 0.25≤x≤0.75.

[0014] Within this ratio range, by controlling the two heterovalent transition metal cations A and B defined in the present invention, the ionic conductivity of the halide solid electrolyte can be further significantly improved, reaching a maximum of more than 4 mS / cm.

[0015] In a second aspect, the present invention provides several preparation schemes of the above-mentioned halide solid electrolyte, wherein the preparation method is selected from one of (a) to (c):

[0016] (a) ball milling a lithium source, a source A and a source B under an inert atmosphere to obtain the halide solid electrolyte;

[0017] (b) grinding the lithium source, source A and source B by hand under an inert atmosphere to obtain a precursor, and then pressing and annealing the precursor to obtain the halide solid electrolyte;

[0018] (c) ball-milling the lithium source, source A and source B under an inert atmosphere to obtain a precursor, and then tableting and annealing the precursor to obtain the halide solid electrolyte.

[0019] Preferably, the method for preparing the halide solid electrolyte is method (c).

[0020] Preferably, the A source and the B source are halide salts, and the lithium source is lithium halide.

[0021] Preferably, the ball milling process is as follows: the ball-to-material ratio is (20-50):1, the ball milling speed is 100-800 rpm / min, and the ball milling time is 15 min-60 h.

[0022] Further preferably, the ball milling speed is 300-600 rpm / min, and the ball milling time is 2-30 h.

[0023] Preferably, the hand grinding process is: grinding in a mortar for 5 minutes to 2 hours. More preferably, the grinding time is 15 minutes.

[0024] Preferably, the annealing temperature is 100-300°C.

[0025] The halide solid electrolyte of the present invention adopts the above-mentioned optimized preparation process, uses shorter ball milling and lower temperature heat treatment, and achieves higher ionic conductivity than the reported halide solid electrolyte containing rare earth metal elements; it is more energy-saving and efficient than the excessively long ball milling time (60h-150h) and higher annealing temperature (300℃-500℃) required in the preparation process of other halides. At the same time, the use of relatively cheap transition metal ions has a considerable cost advantage in large-scale production. It should be noted that the preparation method of the solid electrolyte material of the present invention is not limited to the above-mentioned types. Those skilled in the art can use other commonly used electrolyte material preparation processes for synthesis according to actual needs, as long as it does not affect the composition and use effect of the prepared product.

[0026] In a third aspect, the present invention provides an application of the above-mentioned halide solid electrolyte in the manufacture of all-solid-state batteries.

[0027] Preferably, the application is to provide a lithium-ion battery, wherein the positive electrode material and the electrolyte of the lithium-ion battery include the halide solid electrolyte.

[0028] The high-performance halide solid electrolyte provided by the present invention is used in positive electrode materials and electrolytes to prepare all-solid-state batteries, which can further improve the energy density, help increase the total energy of new energy vehicle battery packs to 400kWh, and exceed 2000km of pure electric mileage; at the same time, it has very excellent battery performance at high rates, which can not only meet the needs of current new energy electric vehicles, but also meet the needs of current fixed large-scale energy storage systems, and has broad market prospects.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] The present invention regulates the concentration of lithium ions and vacancies in the halide electrolyte by high-valent transition metal elements, increases the disorder of cations in the halide electrolyte and the amorphous degree of the halide electrolyte, distorts the sites of cations in the lattice, reduces the energy barrier required in the lithium ion transmission process, and significantly improves the ionic conductivity of the halide solid electrolyte. In addition, the present invention further reduces the manufacturing cost of the new halide solid electrolyte by optimizing the preparation process of the halide solid electrolyte, and mainly solves the problems of low conductivity and complex process of the halide solid electrolyte. The provided halide solid electrolyte can be used for the preparation of positive electrode materials and electrolytes for all-solid-state batteries, which can comprehensively improve battery performance and has high application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The halide solid electrolyte Li of Example 1 1.75 Yb 0.375 Ta 0.625 XRD pattern of Cl6;

[0032] Figure 2 The halide solid electrolyte Li of Example 5 1.25 Hf 0.25 Ta 0.75 Room temperature impedance diagram of Cl6;

[0033] Figure 3 The halide solid electrolyte Li of Example 5 1.25 Hf 0.25 Ta 0.75 Oxidation potential diagram of Cl6;

[0034] Figure 4 The halide solid electrolyte Li of Example 5 1.25 Hf 0.25 Ta 0.75 Battery cycle diagram of Cl6 after 800 cycles of charge and discharge at 2C high rate. DETAILED DESCRIPTION

[0035] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific examples. The test methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are reagents and materials that can be obtained from commercial channels unless otherwise specified.

[0036] In the following embodiments, the preparation method of the halide solid electrolyte is as follows:

[0037] Under the protection of high-purity argon, the raw materials lithium source, source A and source B are weighed according to the molar ratio, the zirconium oxide ball mill is placed in a glove box filled with argon, the weighed raw materials are put into the ball mill, and the ball-to-material ratio (20-50) is 1, the ball milling speed is 300-600rpm / min, and the ball milling is performed for 2-30h. After the high-energy ball milling is completed, the precursor is pressed into a sheet in a glove box filled with argon and placed in a crucible, and annealed at 100-300°C in the protective atmosphere of argon to prepare the halide solid electrolyte.

[0038] Example 1

[0039] An embodiment of the halide solid electrolyte of the present invention, the halide solid electrolyte described in this embodiment is Li 1.75 Yb 0.375 Ta 0.625 Cl6.

[0040] The halide solid electrolyte Li 1.75 Yb 0.375 Ta 0.625 In the preparation method of Cl6, the raw materials LiCl, YbCl3, and TaCl5 are weighed according to a molar ratio of 1.75:0.375:0.625 to prepare the halide solid electrolyte Li 1.75 Yb 0.375 Ta 0.625 Cl6.

[0041] Halide solid electrolyte Li 1.75 Yb 0.375 Ta 0.625 The XRD results of Cl6 are as follows Figure 1 .

[0042] Example 2

[0043] An embodiment of the halide solid electrolyte of the present invention, the halide solid electrolyte described in this embodiment is Li 1.5 Yb 0.25 Ta 0.75 Cl6.

[0044] The preparation method of the halide solid electrolyte described in this embodiment is different from that in embodiment 1 only in that the raw materials LiCl, YbCl3, and TaCl5 are weighed according to a molar ratio of 1.5:0.25:0.75 to prepare the halide solid electrolyte Li 1.5 Yb 0.25 Ta 0.75 Cl6.

[0045] Example 3

[0046] An embodiment of the halide solid electrolyte of the present invention, the halide solid electrolyte described in this embodiment is Li 2.25 Yb 0.625 Ta 0.375 Cl6.

[0047] The preparation method of the halide solid electrolyte described in this embodiment is different from that in embodiment 1 only in that the raw materials LiCl, YbCl3, and TaCl5 are weighed according to a molar ratio of 2.25:0.625:0.375 to prepare the halide solid electrolyte Li 2.25 Yb 0.625 Ta 0.375 Cl6.

[0048] Example 4

[0049] An embodiment of the halide solid electrolyte of the present invention, the halide solid electrolyte described in this embodiment is Li 2.5 Yb 0.75 Ta 0.25 Cl6.

[0050] The preparation method of the halide solid electrolyte described in this embodiment is different from that in embodiment 1 only in that the raw materials LiCl, YbCl3, and TaCl5 are weighed according to a molar ratio of 2.5:0.75:0.25 to prepare the halide solid electrolyte Li 2.5 Yb 0.75 Ta 0.25 Cl6.

[0051] Example 5

[0052] An embodiment of the halide solid electrolyte of the present invention, the halide solid electrolyte described in this embodiment is Li 1.25 Hf 0.25 Ta 0.75 Cl6.

[0053] The preparation method of the halide solid electrolyte described in this embodiment is different from that in embodiment 1 only in that the raw materials LiCl, HfCl4, and TaCl5 are weighed according to a molar ratio of 1.25:0.25:0.75 to prepare the halide solid electrolyte Li 1.25 Hf0.25 Ta 0.75 Cl6.

[0054] Example 6

[0055] An embodiment of the halide solid electrolyte of the present invention, the halide solid electrolyte described in this embodiment is Li 1.5 Hf 0.5 Ta 0.5 Cl6.

[0056] The preparation method of the halide solid electrolyte described in this embodiment is different from that in embodiment 1 only in that the raw materials LiCl, HfCl4, and TaCl5 are weighed according to a molar ratio of 1.5:0.5:0.5 to prepare the halide solid electrolyte Li 1.5 Hf 0.5 Ta 0.5 Cl6.

[0057] Example 7

[0058] An embodiment of the halide solid electrolyte of the present invention, the halide solid electrolyte described in this embodiment is Li 1.7 Hf 0.7 Ta 0.3 Cl6.

[0059] The preparation method of the halide solid electrolyte described in this embodiment is different from that in embodiment 1 only in that the raw materials LiCl, HfCl4, and TaCl5 are weighed according to a molar ratio of 1.7:0.7:0.3 to prepare the halide solid electrolyte Li 1.7 Hf 0.7 Ta 0.3 Cl6.

[0060] Example 8

[0061] An embodiment of the halide solid electrolyte of the present invention, the halide solid electrolyte described in this embodiment is Li 1.875 Hf 0.875 Ta 0.125 Cl6.

[0062] The preparation method of the halide solid electrolyte described in this embodiment is different from that in embodiment 1 only in that the raw materials LiCl, HfCl4, and TaCl5 are weighed according to a molar ratio of 1.875:0.875:0.125 to prepare the halide solid electrolyte Li 1.875 Hf 0.875 Ta 0.125 Cl6.

[0063] Example 9

[0064] An embodiment of the halide solid electrolyte of the present invention, the halide solid electrolyte described in this embodiment is Li 1.9 Hf 0.9 Ta 0.1 Cl6.

[0065] The preparation method of the halide solid electrolyte described in this embodiment is different from that in embodiment 1 only in that the raw materials LiCl, HfCl4, and TaCl5 are weighed according to a molar ratio of 1.9:0.9:0.1 to prepare the halide solid electrolyte Li 1.9 Hf 0.9 Ta 0.1 Cl6.

[0066] Example 10

[0067] An embodiment of the halide solid electrolyte of the present invention, the halide solid electrolyte described in this embodiment is Li2Y 0.5 Ta 0.5 Cl6.

[0068] The preparation method of the halide solid electrolyte described in this embodiment is different from that in embodiment 1 only in that the raw materials LiCl, YCl3, and TaCl5 are weighed according to a molar ratio of 2:0.5:0.5 to prepare the halide solid electrolyte Li2Y 0.5 Ta 0.5 Cl6.

[0069] Embodiment 11

[0070] An embodiment of the halide solid electrolyte of the present invention, the halide solid electrolyte described in this embodiment is Li 2.25 Y 0.625 Ta 0.375 Cl6.

[0071] The preparation method of the halide solid electrolyte described in this embodiment is different from that in embodiment 1 only in that the raw materials LiCl, YCl3, and TaCl5 are weighed according to a molar ratio of 2.25:0.625:0.375 to prepare the halide solid electrolyte Li 2.25 Y 0.625 Ta 0.375 Cl6.

[0072] Comparative Example 1

[0073] A solid electrolyte LiTaCl6, the preparation method of which is different from that of Example 1 only in that:

[0074] The raw materials LiCl and TaCl5 were weighed in a molar ratio of 1:1 to prepare the halide solid electrolyte LiTaCl6.

[0075] Comparative Example 2

[0076] A solid electrolyte Li3YbCl6, the preparation method of which is different from that of Example 1 only in that:

[0077] The raw materials LiCl and YbCl3 were weighed in a molar ratio of 3:1 to prepare the halide solid electrolyte Li3YbCl6.

[0078] Comparative Example 3

[0079] A solid electrolyte Li2HfCl6, the preparation method of which is different from that of Example 1 only in that:

[0080] The raw materials LiCl and HfCl4 were weighed in a molar ratio of 2:1 to prepare the halide solid electrolyte Li2HfCl6.

[0081] Comparative Example 4

[0082] A solid electrolyte Li3YCl6, the preparation method of which is different from that of Example 1 only in that:

[0083] The raw materials LiCl and YCl3 were weighed in a molar ratio of 3:1 to prepare the halide solid electrolyte Li3YCl6.

[0084] Effect Example 1

[0085] In order to explore the conductivity of the halide solid electrolyte provided by the present invention, impedance tests were performed on the solid electrolytes in the embodiments and comparative examples: an electrochemical workstation was used to perform an AC impedance test, and a peek mold with a diameter of 10 mm was used, with both the upper and lower sides made of stainless steel. 100 mg of halide solid electrolyte powder was evenly placed in the mold, and a conductivity test was performed under a pressure of 1.5 tons.

[0086] Example 5 Halide Solid Electrolyte Li 1.25 Hf 0.25 Ta 0.75 The room temperature impedance results of Cl6 are as follows Figure 2 The ionic conductivity results of all solid electrolytes in the examples and comparative examples are shown in Table 1.

[0087] From Table 1, we can see that:

[0088] (1) The halide solid electrolyte in the embodiment of the present invention conforms to the chemical formula Li 1+(5-n)x A x B 1-x Cl6 and n = 3 or n = 4, 0.1 ≤ x ≤ 0.9, the ionic conductivity is ≥ 0.80 mS / cm, which is significantly higher than the electrolyte in the comparative example. 1.25 Hf 0.25 Ta0.75 The ion conductivity of Cl6 halide solid electrolyte is the highest, reaching over 4mS / cm.

[0089] (2) From the comparison of Examples 10 and 11 with Comparative Example 4, it can be seen that the solid electrolyte containing a single transition metal cation as defined in the present invention has a relatively low ionic conductivity, with a maximum of only 0.13 mS / cm. However, by introducing transition metal cations within the scope defined in the present invention and adjusting the ratio of the two heterovalent transition metal cations, the ionic conductivity of the halide solid electrolyte can be significantly improved to above 0.80 mS / cm.

[0090] (3) From the comparison between Examples 1-9 and Comparative Examples 1-3, it can be seen that the optimization of transition metal cations and their ratios in Examples 5-9 can significantly improve the ionic conductivity of the halide solid electrolyte; the introduction of two specific heterovalent transition metal cations and their ratios in Example 5 can further significantly improve the ionic conductivity, which can reach 4.50 mS / cm.

[0091] Table 1 Ionic conductivity results of halide solid electrolytes in Examples and Comparative Examples

[0092] Serial number Chemical formula Ionic conductivity (mS / cm) Example 1 <![CDATA[Li 1.75 Yb 0.375 The 0.625 Cl6]]> 1.98 Example 2 <![CDATA[Li 1.5 Yb 0.25 The 0.75 Cl6]]> 0.93 Example 3 <![CDATA[Li 2.25 Yb 0.625 The 0.375 Cl6]]> 1.52 Example 4 <![CDATA[Li 2.5 Yb 0.75 The 0.25 Cl6]]> 0.85 Example 5 <![CDATA[Li 1.25 Hf 0.25 I 0.75 Cl6]]> 4.50 Example 6 <![CDATA[Li 1.5 Hf 0.5 I 0.5 Cl6]]> 3.74 Example 7 <![CDATA[Li 1.7 Hf 0.7 I 0.3 Cl6]]> 1.75 Example 8 <![CDATA[Li 1.875 Hf 0.875 I 0.125 Cl6]]> 0.96 Example 9 <![CDATA[Li 1.9 Hf 0.9 I 0.1 Cl6]]> 0.87 Example 10 <![CDATA[Li2Y 0.5 I 0.5 Cl6]]> 0.80 Embodiment 11 <![CDATA[Li 2.25 Y 0.625 I 0.375 Cl6]]> 1.02 Comparative Example 1 <![CDATA[LiTaCl6]]> 0.0007 Comparative Example 2 <![CDATA[Li3YbCl6]]> 0.0176 Comparative Example 3 <![CDATA[Li2HfCl6]]> 0.22 Comparative Example 4 <![CDATA[Li3YCl6]]> 0.13

[0093] Effect Example 2

[0094] In order to explore the application effect of the halide solid electrolyte provided by the present invention in the battery, the halide solid electrolyte Li 1.25 Hf 0.25 Ta 0.75 Cl6 was tested as follows:

[0095] a. Oxidation potential: AC impedance and oxidation potential tests were performed using an electrochemical workstation. Example 5 Halide solid electrolyte Li 1.25 Hf 0.25 Ta 0.75 The room temperature impedance and oxidation potential results of Cl6 are shown in Figure 2 , 3 .

[0096] b. Further preparation of all-solid-state batteries and testing of performance:

[0097] The composite positive electrode is made of NCM811, VGCF (carbon fiber) and the halide solid electrolyte prepared in Example 5, which are uniformly mixed in an agate mortar at a mass ratio of 65:3:32, and then manually ground for 1 hour or mixed in a mixer for 30 minutes. The assembly steps of the all-solid-state battery are as follows: 40 mg of Li6PS5Cl powder is placed in a peek mold with a diameter of 10 mm, and a pressure of 1.5 tons is applied and maintained for 2 minutes; then 70 mg of the halide solid electrolyte is evenly spread on the sulfide, and a pressure of 1.5 tons is applied and maintained for 2 minutes; then 7.5 mg of the composite positive electrode powder is evenly spread on the halide solid electrolyte, and a pressure of 2 tons is applied and maintained for 2 minutes; finally, Li-In alloy is placed on one side of the sulfide, and the In side is preferentially attached to the sulfide side, and is placed in a pressure holder to apply a pressure of 1.5 tons and maintain. The full battery test is carried out on a blue electric constant current charge and discharge test. The halide solid electrolyte Li of Example 5 1.25 Hf 0.25 Ta 0.75 The battery cycle results of Cl6 at 2C high rate charge and discharge for 800 cycles are as follows Figure 4 .

[0098] Depend on Figure 3 It can be seen that the halide solid electrolyte prepared in the present invention has a higher oxidation potential (Li 1.25 Hf 0.25 Ta 0.75 The oxidation potential of Cl6 is greater than 4.0V). The application of high-nickel high-voltage positive electrode can further improve the energy density of all-solid-state batteries, help increase the total energy of new energy vehicle battery packs to 400kWh, and the pure electric cruising range exceeds 2000km, which has high application value in the field of new energy vehicles.

[0099] Depend on Figure 4 It can be seen that the halide solid electrolyte provided by the present invention has very excellent battery performance at a high rate of 2C (1C = 200mAh / g), providing a new and good solution for future high energy density fast charging batteries, and has high application value in the solid-state battery manufacturing industry.

[0100] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A halide solid electrolyte, characterized in that: The halide solid electrolyte is Li 1+(5-n)x A x B 1-x Cl6, A is at least one of Yb, Y, and Hf, B is at least one of Ta and Nb; n=3 or n=4; 0.1≤x≤0.

9.

2. The halide solid electrolyte according to claim 1, characterized in that The A is at least one of Yb and Hf, and the B is at least one of Ta and Nb.

3. The halide solid electrolyte according to claim 2, characterized in that The 0.25≤x≤0.

75.

4. The halide solid electrolyte according to claim 3, characterized in that The ion conductivity of the halide solid electrolyte is ≥0.85 mS / cm.

5. The method for preparing the halide solid electrolyte according to any one of claims 1 to 4, characterized in that: The preparation method is selected from one of (a) to (c): (a) ball milling a lithium source, a source A and a source B under an inert atmosphere to obtain the halide solid electrolyte; (b) grinding the lithium source, source A and source B by hand under an inert atmosphere to obtain a precursor, and then pressing and annealing the precursor to obtain the halide solid electrolyte; (c) ball-milling the lithium source, source A and source B under an inert atmosphere to obtain a precursor, and then tableting and annealing the precursor to obtain the halide solid electrolyte.

6. The method for preparing a halide solid electrolyte according to claim 5, characterized in that: The A source and the B source are halide salts, and the lithium source is lithium halide.

7. The method for preparing a halide solid electrolyte according to claim 5, characterized in that: The ball milling process is as follows: the ball-to-material ratio is (20-50):1, the ball milling speed is 100-800 rpm / min, and the ball milling time is 15 min-60 h.

8. The method for preparing a halide solid electrolyte according to claim 5, characterized in that: The hand grinding process is: grinding in a mortar, and the grinding time is 5 minutes to 2 hours.

9. The method for preparing a halide solid electrolyte according to claim 5, characterized in that: The annealing temperature is 100-300°C.

10. Use of the halide solid electrolyte according to any one of claims 1 to 4 in the manufacture of all-solid-state batteries.

Citation Information

Patent Citations

  • Composite halide solid electrolyte as well as preparation method and application thereof

    CN110970667A

Cited By

  • High-valence cation doped amorphous dominant halide solid electrolyte as well as preparation method and application thereof

    CN122474687A